Edukasi Perilaku Hidup Bersih dan Sehat Dimasa Pandemi Covid-19 Di Lingkungan Asrama Universitas Dharmas Indonesia - Sukmawati; Sri Andar Puji Astuti; Siti Khotimah; Evin Noviana Sari (Pucuk Rebung: Jurnal Pengabdian kepada Masyarakat, 2021)
Clean and healthy living behaviour is a behaviour that is practised in everyday life. The purpose of implementing clean and healthy living behaviour in the dormitory environment is so that the dormitory community continues to apply a clean and healthy lifestyle during the COVID-19 pandemic so as to prevent transmission in the dormitory environment. The approach to overcome partner problems is through counselling and mentoring methods as well as providing facilities and infrastructure to support the implementation of clean and healthy living behaviours. The implementation of this community service activity is carried out in all dormitory buildings of Dharmas Indonesia University. Implementation of activities is counselling about clean and healthy living behaviour which includes counselling about clean and healthy living behaviour and implementation of clean and healthy living behaviour, as well as healthy exercise. Then cleaning is done throughout the dormitory environment. In addition, activities for clean and healthy living behaviour through mutual cooperation activities are carried out every Sunday. The benefits of gymnastics have been felt by the dormitory community, such as improving sleep quality, being able to relieve stress, and controlling weight.